PENGEMBANGAN MODUL PEMBELAJARAN SISTEM REPRODUKSI BERAZASKAN AL-QURAN/HADIS UNTUK MENINGKATKANMOTIVASI DAN HASIL BELAJAR PESERTA DIDIK - Dian Agusti; Hafnati Rahmatan; Sulastri Sulastri (EDUSAINS, 2019)
DEVELOPMENT OF REPRODUCTIVE SYSTEM MODULE WITH AL-QURAN/HADITH TO IMPROVE MOTIVATION AND STUDENT LEARNING OUTCOMESDian Agusti, Hafnati Rahmatan, SulastriUniversitas Syiah Kuala, Aceh, Indonesia uyankdian@gmail.comAbstractThe purpose of this study was to describe the differences in the results and motivation learning of experimental and control class on the subject of the reproductive system by using modules based on the Al-Quran and hadith. This research is a development research using the Borg and Gall models. Learning devices developed modules questions. The results of the feasibility test indicate that the modull of Al-Quran based learning and the hadith developed are included in the very feasible category, with the average score of the feasibility assessment of design validation, the results of the first trial and the results of the second trial of 3.91, 4 54 and 4.83. Data analysis using t test, with sig value <0.05, which means there are significant differences in learning outcomes in the experimental  and  control class. The average score of learning motivation of students at Labuhanhaji 1 Junior and West Labuhanhaji 1 Junior High School are respectively 4.56 and 4.55 which are very well categorized. Based on the results of the study it can be concluded that the learning module based on the Koran and hadith can increase the motivation and learning outcomes of students, especially on reproductive system material. AbstrakTujuan penelitian ini adalah mendeskripsikan perbedaan hasil dan motivasi belajar peserta didik kelas eksperimen dan kontrol pada pokok bahasan sistem reproduksi menggunakan modul berazaskan Al-Quran dan hadis. Penelitian ini merupakan kajian pengembangan menggunakan model Borg dan Gall. Perangkat pembelajaran yang dikembangkan modul. Hasil uji kelayakan menunjukkan bahwa modul pembelajaran  yang dikembangkan termasuk dalam kategori sangat layak, dengan skor rata-rata penilaian kelayakan validasi desain, hasil uji coba I dan hasil uji coba II berturut-turut sebesar 3,91, 4,54 dan 4,83.  Analisis data menggunakan uji t, dengan nilai sig.<0,05 yang berarti terdapat perbedaan yang signifikan terhadap hasil belajar pada kelas eksperimen dan kontrol. Skor rata-rata motivasi belajar peserta didik pada SMPN 1 Labuhanhaji dan SMPN 1 Labuhanhaji Barat berturut-turut  sebesar 4,56 dan 4,55 berkategori sangat baik. Berdasarkan hasil penelitian dapat disimpulkan bahwa modul pembelajaran berazaskan Al-Quran dan hadis dapat meningkatkan motivasi dan hasil belajar peserta didik khususnya pada materi sistem reproduksi.